High ecological health risks of potentially toxic metals in polluted drainage sediments: Is there a need for public concern during flash floods? - Chee, Kong Yap; Al-Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute, 2022)
The present study aimed to investigate the concentrations of potentially toxic metals (PTMs) in the drainages, rivers, and coast of Malacca in Peninsular Malaysia. The ranges of total PTM concentrations (mg/kg dry weight) were 1.88–7.01 for Cd, 18.9–1689 for Cu, 26.0–850 for Ni, 56.5–307 for Pb, and 75.4–312 for Zn. Based on an ecological risk assessment and geochemical fractions, it was concluded that heavy metals pollute the drainages and the Malacca River. The potential ecological risk index (PERI) categorised the drainage and river sites as a “very high ecological risk”. Therefore, it was shown that elevated levels of PTMs in the drainages near Malacca Industrial Area and in the Malacca River sediment were most probably attributed to untreated (or incomplete treatment of) industrial effluents. The drainage sediments were found to have higher hazard quotient (HQ) values for the three pathways of the PTMs for children and adults. Although in general, the non-carcinogenic risks of the PTMs for children and adults indicated no significant detrimental health effects, the hazard index (HI) for Pb in children at drainage locations surpassed 1.0, suggesting a non-carcinogenic risk (NCR), which is a cause for worry. Consequently, the ecological health risk assessments offered critical information for PTM pollution reduction and environmental management in future sustainable development initiatives in Peninsular Malaysia’s drainages and rivers. The present findings on the ecological health risks of PTMs based on 2006 samples can serve as an important baseline for future reference and comparison. This work should encourage future investigations on the direct impact of the risks to the residents during floods in Malaysia, as part of mitigation and risk assessments of the contaminated drainage and river sediments in an attempt to lower the hazards for the surrounding residents.